2019
DOI: 10.1038/s41598-019-45113-2
|View full text |Cite
|
Sign up to set email alerts
|

The spatial parameters of gait and their association with falls, functional decline and death in older adults: a prospective study

Abstract: Association between spatial gait parameters and adverse health outcomes in the elderly has not been sufficiently studied. The goal of this study is to evaluate whether the stride length or the step width predict falls, functional loss and mortality. We conducted a prospective cohort study on a probabilistic sample of 431 noninstitutionalized, older-than-64-years subjects living in Spain, who were followed-up for five years. In the baseline visit, spatial gait parameters were recorded along with several control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
2
19
1
2
Order By: Relevance
“…Based on this research, the WR can detect older people with a risk of falling who show normal gait speed. Step length, on the other hand, is associated with functional loss and falls [ 40 ]. This demonstrates the potential benefits of including additional gait parameters in a mobility analysis of older people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this research, the WR can detect older people with a risk of falling who show normal gait speed. Step length, on the other hand, is associated with functional loss and falls [ 40 ]. This demonstrates the potential benefits of including additional gait parameters in a mobility analysis of older people.…”
Section: Discussionmentioning
confidence: 99%
“…Dibble et al (2006) reported an improved inter-tester reliability [38] when using automated measurements. Furthermore, as gait parameters such as cadence [39] or step length [40] can provide additional information on functional ability, automated systems should be able to identify such parameters. However, the use of such technical measurement systems have their own challenges.…”
Section: Introductionmentioning
confidence: 99%
“…evaluations by clinicians(e.g. the Tinetti test 4 or the timed up and go test 5 ), but, it can be further objectified with biomechanical analysis in a laboratory 2 . Kinetics variables (the forces that cause the body to move) must be collected in a laboratory environment with force plates (e.g.…”
Section: Best Regardsmentioning
confidence: 99%
“…The loss of gait or its alteration with pathological conditions are known to be related to mortality, especially in the elderly (e.g. 4,5), stressing the importance of addressing gait disorders in physiotherapy. Gait requires body propulsion and balance control for safe progression, two "subtasks" that require the coordination of multiple skeletal muscles and the integration of sensory information arising from the vestibular, visual and somatosensory systems [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…A good deal of research demonstrates a close association between cognitive decline and mobility limitation (Ambrose et al, 2010;Mielke et al, 2013;Pedersen et al, 2014;Rodriguez-Molinero et al, 2019). For example, walking may seem like a simple task but it is quite complex.…”
Section: Introductionmentioning
confidence: 99%